Eco-innovation and sustainable business performance: The moderating effect of market turbulence on tupperware in Indonesia - Miranda, Fina; Ramadania, Ramadania; Pebrianti, Wenny; Rosnani, Titik; Syahbandi, Syahbandi (Enrichment : Journal of Management, 2023)
Waste that accumulates and is not recycled can have a negative impact on the environment, people's lives and health. This has made some people more selective in choosing and buying everyday products, and many are starting to switch to using environmentally friendly and sustainable products. This change is an opportunity for companies to make products that use environmentally friendly production raw materials and are safe for health. This research will examine how eco-innovation (eco-process, eco-product, and eco-organizational) can influence sustainable business performance with market turbulence as a moderating variable for Tupperware products in Indonesia. This research involved 211 people from various regions in Indonesia who were collected online using purposive sampling techniques via questionnaires. Data were analyzed using Structural Equation Modeling (SEM) using AMOS 24. The research results show that eco-process innovation, eco-product innovation and eco-organizational innovation positively and significantly affect sustainable business performance. Meanwhile, market turbulence as a moderator negatively and significantly influences sustainable business performance.